RELIGIUSITAS MASYARAKAT ADAT KAMPUNG DUKUH KABUPATEN GARUT JAWA BARAT - M. Rahmat Effendi; Edi Setiadi; Nandang HMZ (IAIN Salatiga, 2018)
This paper aims to examine: (1) religious expressions, (2) religious patterns, and (3) religious values’ conservation in addressing to the challenges of modernization of an indigenous communities at Kampung (Village) Dukuh through the symbols of their lives. Due to religion as a cultural system has become a symbolic system that offers a way to perceive the world. Religion as a “mode of is for reality” provides a “framework” to see the reality, religion also provides a “system of meaning” for their followers which is socially constructed. The indigenous community of Kampung Dukuh tends to make “religion” as their “ultimate concern”. They believe that religion has become their fundamental philosophy for their lives. Most of their activities are according to the religious values. AbstrakTulisan ini bertujuan ingin mengkaji tentang: (1) Ekspresi keberagamaan, (2) Pola keberagamaan, dan (3) Konservasi nilai-nilai agama dalam menghadapi tantangan modernisasi pada masyarakat adat Kampung Dukuh melalui simbol-simbol dalam kehidupan mereka. Karena agama sebagai sistem budaya merupakan sistem simbolik yang menawarkan cara untuk mempersepsi dunia. Agama sebagai ”mode is for reality” memberikan ”framework” untuk melihat realilas, agama menyediakan ”system of meaning” bagi penganutnya yang diproduksi secara sosial. Masyarakat adat Kampung Dukuh cenderung menjadikan “agama” sebagai “the ultimate concern”. Mereka menjadikan agama sebagai filosofi mendasar dalam kehidupan mereka. Hampir seluruh aktifitas dalam kehidupan mereka didasarkan pada nilai-nilai agama.